Β-Elemene-Attenuated Tumor Angiogenesis by Targeting Notch-1 in Gastric Cancer Stem-Like Cells. (9th April 2013) - Yan, Bing; Zhou, Yuqi; Feng, Shouhan; Lv, Can; Xiu, Lijuan; Zhang, Yingcheng; Shi, Jun; Li, Yongjin; Wei, Pinkang; Qin, Zhifeng
Abstract : Emerging evidence suggests that cancer stem cells are involved in tumor angiogenesis. The Notch signaling pathway is one of the most important regulators of these processes. β -Elemene, a naturally occurring compound extracted from Curcumae Radix, has been used as an antitumor drug for various cancers in China. However, its underlying mechanism in the treatment of gastric cancer remains largely unknown. Here, we report that CD44+ gastric cancer stem-like cells (GCSCs) showed enhanced proliferation capacity compared to their CD44− counterparts, and this proliferation was accompanied by the high expression of Notch-1 ( in vitro ). These cells were also more superior in spheroid colony formation ( in vitro ) and tumorigenicity ( in vivo ) and positively associated with microvessel density ( in vivo ). β -Elemene was demonstrated to effectively inhibit the viability of GCSCs in a dose-dependent manner, most likely by suppressing Notch-1 ( in vitro ). β -Elemene also contributed to growth suppression and attenuated the angiogenesis capacity of these cells ( in vivo ) most likely by interfering with the expression of Notch-1 but not with Dll4. Our findings indicated that GCSCs play an important role in tumor angiogenesis, and Notch-1 is one of the most likely mediators involved in these processes. β -Elemene was effective at attenuating angiogenesis by targeting the GCSCs, which could be regarded as a potential mechanism for its efficacy in gastric cancer management in the future.